Reconfiguring Islamic Religious Authority: The Muhammadiyah Model for Gender Equality Reform in a Global Context - M. Nurdin Zuhdi (Journal Discrimination and Injustice, 2025)
This article examines Ki Hadjar Dewantara’s (KHD) contribution to early gender equality discourse in Indonesia through his writings in Madjallah Wasita magazines (1928–1935), produced in a socio-cultural context dominated by patriarchal norms and limited public awareness of women’s rights. In addition to analyzing KHD’s views on women, the study aims to assess the relevance of his thought for the development of gender reform within Islamic and educational thought in Indonesia and to situate it in dialogue with the Muhammadiyah Model for Gender Equality Reform in a Global Context. Employing a qualitative approach grounded in historical discourse analysis and informed by Muslim feminist theory, this research examines selected texts published in Madjallah Wasita as primary sources, supported by relevant secondary literature. This framework enables a contextual reading of gender, education, and moral discourse within early Indonesian reform movements. Findings indicate that KHD articulated three key ideas. First, he emphasized women’s role as mothers as a moral foundation of society, framing motherhood as a source of dignity rather than subordination. Second, he strongly advocated higher education for women as a prerequisite for national progress. Third, he affirmed women’s right to participate in the public sphere, including access to decent work, while maintaining ethical and social norms. These ideas resonate with the Muhammadiyah model, particularly in conceptualizing gender equality as compatible with religious values, educational reform, and social responsibility. The study concludes that KHD advanced a progressive and context-sensitive vision of gender relations that both preceded and complemented later Islamic reform movements, including Muhammadiyah’s transnational approach to faith-based gender equality. It recommends integrating KHD’s gender-inclusive educational philosophy into national education policies, teacher training, and gender-responsive curricula to strengthen contemporary reforms on gender equality and religious authority.